URGENSI BIMBINGAN DAN KONSELING PADA ANAK USIA DINI DALAM MENANAMKAN PENDIDIKAN GENDER - Sopiah, Ai Durotuss (AflahConsilia : Jurnal Bimbingan dan Konseling, 2024)
Guidance and counseling teachers in the educational environment are important, because the existence of guidance and counseling teachers not only helps in all aspects related to children's behavioral problems but can be a support and shaper and provider of knowledge in aspects of children's social development, especially in the realm of gender. This research uses literature study research with a descriptive analysis approach. The result of the research is that the discovery of identity for children of guidance and counseling teachers becomes a driving force in finding it. Early childhood is a golden age, which is the initial period in the formation of all aspects of children's lives and the growth and development of the potential possessed by children. From the age of 0-6 years, understanding of gender for early childhood needs to be applied as early as possible. Because at that age the child's growth and development is in its rapid phase. Positive stimulus is needed by children because learning in childhood will affect the development of children in the future.